2014
DOI: 10.7554/elife.02743
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific processing of social cues in the medial amygdala

Abstract: Animal–animal recognition within, and across species, is essential for predator avoidance and social interactions. Despite its essential role in orchestrating responses to animal cues, basic principles of information processing by the vomeronasal system are still unknown. The medial amygdala (MeA) occupies a central position in the vomeronasal pathway, upstream of hypothalamic centers dedicated to defensive and social responses. We have characterized sensory responses in the mouse MeA and uncovered emergent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
199
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(223 citation statements)
references
References 86 publications
(156 reference statements)
15
199
2
Order By: Relevance
“…FG-7142 induced a significant level of social anxiety which was blunted by icv RXFP3-A2 treatment; but as this effect did not reach statistical significance, further studies are warranted to better determine the robustness of the involvement of relaxin-3/RXFP3 signalling in the control of social anxiety. In this regard, while a dissociation of actions on social and general anxiety has been reported for other neuropeptide/receptor systems such as neuropeptide S/NPSR [58] and in certain genetic disorders [59], high levels of RXFP3 mRNA are present in brain areas relevant to social behaviour control in mice including the olfactory bulb, medial amygdala, and ventral hypothalamus [36,[60][61][62][63] (see Allen Brain Atlas, <www.brain-map.org>).…”
Section: Discussionmentioning
confidence: 99%
“…FG-7142 induced a significant level of social anxiety which was blunted by icv RXFP3-A2 treatment; but as this effect did not reach statistical significance, further studies are warranted to better determine the robustness of the involvement of relaxin-3/RXFP3 signalling in the control of social anxiety. In this regard, while a dissociation of actions on social and general anxiety has been reported for other neuropeptide/receptor systems such as neuropeptide S/NPSR [58] and in certain genetic disorders [59], high levels of RXFP3 mRNA are present in brain areas relevant to social behaviour control in mice including the olfactory bulb, medial amygdala, and ventral hypothalamus [36,[60][61][62][63] (see Allen Brain Atlas, <www.brain-map.org>).…”
Section: Discussionmentioning
confidence: 99%
“…The MeA is still maturing during the postweaning period (Schulz et al, 2009;Cooke, 2011;De Lorme et al, 2012;Bergan et al, 2014). Social isolation can stunt the maturation of other brain regions (Sanchez et al, 1995;Helmeke et al, 2001;Lapiz et al, 2003;Gos et al, 2006;Agis-Balboa et al, 2007;Gilabert-Juan et al, 2012;Makinodan et al, 2012).…”
Section: Social Isolation Impairs Medial Amygdala T Adams and Ja Rosementioning
confidence: 99%
“…The medial nucleus of the amygdala (MeA) has been particularly implicated in prosocial maternal and sexual behavior, as well as agonistic aggressive behaviors. In rodent models, the MeA is activated by socially relevant cues, such as maternal interaction, mating, pheromones of opposite-sex conspecifics, and predators (Fleming and Walsh, 1994;Kollack-Walker and Newman, 1997;Meredith and Westberry, 2004;Choi et al, 2005;Samuelsen and Meredith, 2009b;Bergan et al, 2014), ablation of the MeA impairs recognition of opposite-sex odors (Petrulis, 2009;Maras and Petrulis, 2010), and activation of MeA afferents induces a gradient of social behavior from mating behavior to aggression (Hong et al, 2014;Unger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Érdi and Czirják's solution to a large subclass of the central four-body problem is a major advance that encompasses and greatly extends many previous four-body results, including: arrangements of four 2 and three 3 identical masses; kite-shaped configurations of diagonally opposite pairs of equal masses 4 ; and the limiting case of three bodies plus a massless test particle 5 . Just as three-body configurations serve as limiting cases for Érdi and Czirják's four-body configurations, the authors' solutions could, in turn, be used as limiting cases for ambitious future extensions of the n-body problem: perhaps three masses along a line plus two symmetrically placed equal masses; a test particle plus planar configurations of the type considered in the present work; or even planar arrangements of four different masses.…”
mentioning
confidence: 66%
“…There are clearly male-female differences in some brain regions, but these can be subtle and variable, and their causes and consequences remain largely unclear. Over the past five years, work in several organisms [1][2][3] has suggested that altered neural connectivity between brain regions might be a hallmark of male-female differences. On page 206 of this issue, Oren-Suissa et al 4 provide clear evidence for sex differences in neural wiring in the roundworm Caenorhabditis elegans.…”
Section: Douglas P Hamilton Is In the Departmentmentioning
confidence: 99%